Sulfur-Chelated Ruthenium Olefin Metathesis Catalysts - Nechmad, Noy B.; Lemcoff, N. Gabriel (Synlett, 2021)
This Account summarizes the historical development of latent sulfur-chelated ruthenium precatalysts from the Lemcoff group’s perspective. The most unique feature of this family of complexes is that they appear in the more stable cis-dichloro configuration, which is latent towards olefin metathesis reactions. Activation of the precatalyst, brought about by isomerization from the cis-dihalo to the trans-dihalo forms, can be achieved either by thermal or light stimuli. Modifications of the ligand sphere bestows unique properties upon the catalysts, which have been used in diverse applications, from 3D printing of metathesis polymers to orthogonally divergent synthetic pathways.1 Introduction2 Effect of Sulfur Substituents3 Effect of Benzylidene Ligands4 Effect of the NHC Ligands5 Effect of the Anionic Ligands6 Conclusions
Keywords: olefin metathesis; ruthenium catalyst; latency; sulfur-chelated benzylidene; ligand design